Iowa RBA, February 9, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Email for the Iowa RBA for February 9, 1998. Highlights include Common Raven, Snowy Owl, Common and Hoary Redpolls, California, Glaucous and Lesser Black-backed Gulls, and Eurasian Collared Dove. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed